Computational Fluid Dynamics‐Based Design Optimization Method for Archimedes Screw Blood Pumps. Issue 4 (2nd November 2015) - Yu, Hai; Janiga, Gábor; Thévenin, Dominique
Abstract: An optimization method suitable for improving the performance of Archimedes screw axial rotary blood pumps is described in the present article. In order to achieve a more robust design and to save computational resources, this method combines the advantages of the established pump design theory with modern computer‐aided, computational fluid dynamics (CFD)‐based design optimization (CFD‐O) relying on evolutionary algorithms and computational fluid dynamics. The main purposes of this project are to: (i) integrate pump design theory within the already existing CFD‐based optimization; (ii) demonstrate that the resulting procedure is suitable for optimizing an Archimedes screw blood pump in terms of efficiency. Results obtained in this study demonstrate that the developed tool is able to meet both objectives. Finally, the resulting level of hemolysis can be numerically assessed for the optimal design, as hemolysis is an issue of overwhelming importance for blood pumps.